2010
DOI: 10.2217/pgs.10.106
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Excision Repair Gene Polymorphisms May Predict Acute Toxicity in Patients Treated with Chemoradiotherapy for Bladder Cancer

Abstract: These results suggest that nucleotide excision repair gene polymorphisms, especially in XPC, might potentially be predictive factors for acute toxicity of CRT for bladder cancer, helping individual patient selection for bladder conservation therapy. However, further studies with larger sample sizes are needed to draw final conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 37 publications
1
35
0
1
Order By: Relevance
“…The patients received combined platinum-based systemic CRT. In the majority of patients, one cycle of the regimen (based on Shipley's method with slight modification) (17) included administration of cisplatin (70 mg̸m 2 ) on day 1, followed by radiation at 1.8 Gy per fraction on days 2-5 in the first week and every 5 days consecutively in the second week (18)(19)(20). Radiotherapy involved 10-MV photons with a 4-field technique, treating the bladder and pelvic lymph nodes to 32.4 Gy during 2 cycles, followed by a CT-planned whole-bladder boost of 16.2 Gy for an additional cycle.…”
Section: Methodsmentioning
confidence: 99%
“…The patients received combined platinum-based systemic CRT. In the majority of patients, one cycle of the regimen (based on Shipley's method with slight modification) (17) included administration of cisplatin (70 mg̸m 2 ) on day 1, followed by radiation at 1.8 Gy per fraction on days 2-5 in the first week and every 5 days consecutively in the second week (18)(19)(20). Radiotherapy involved 10-MV photons with a 4-field technique, treating the bladder and pelvic lymph nodes to 32.4 Gy during 2 cycles, followed by a CT-planned whole-bladder boost of 16.2 Gy for an additional cycle.…”
Section: Methodsmentioning
confidence: 99%
“…[31][32][33] However, such studies using cell lines could not replicate the findings from population-based studies, which had reported significant associations between SNPs in multiple genes (eg, drug metabolism genes, DNA repair genes, and apoptosis genes) and the toxicity response. [34][35][36][37] This difference might have resulted from different mechanisms underlying the toxicity responses of the 2 levels (cell line and individual). The p53 pathway plays important roles in chemotherapy response and cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…The association between the functional SNP T309G (rs2279744) and platinum-based or noneplatinum-based chemotherapy responses has been investigated in many cancers. 18,35,[40][41][42][43] However, the results have been inconsistent regarding the effects of this SNP on gastrointestinal and hematologic toxicities. No significant effects were found in 136 patients with bladder cancer who received combined cisplatinbased systemic chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…carriership of polymorphisms in the XPD, ERCC1 and XRCC1 genes conferring lower capacity for DnA repair has been shown to be associated with higher risk for acute and late toxicity in 'standard' chemotherapy or radiotherapy regimens (40,59). What is more, polymorphic variants of genes which are not known to be associated with substantial decrease in the capacity for DnA repair may apparently also modify the risk for toxicity following anticancer therapy, as the R allele of the P72R polymorphism has been found to be more frequent in vascular skin lesions following radiotherapy for breast cancer than the P allele (61).…”
Section: Using Information About Individual Repair Capacity For Desigmentioning
confidence: 99%